Pelatihan Penggunaan Aplikasi Merdeka Mengajar untuk Meningkatkan Literasi dan Keterampilan Digital Guru Sekolah Dasar - Yasinta Bella Fitriana; Nur Fitrianingsih Hasan; Masni Sanmas; Rizky Nurbarokah Tarmino; Rahman (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The lack of knowledge and digital skills of teachers in searching for references for teaching materials has resulted in the Merdeka Mengajar Application provided by the Ministry of Education and Culture not being used optimally. Teachers have difficulty learning and using the Merdeka Mengajar application due to the lack of socialization and tutorials. Apart from that, when conducting online learning, partners only use Zoom and WhatsApp media, they are not yet familiar with using the Learning Management System. Apart from teachers and students, the school does not yet have a profile website so digital culture has not been implemented properly. The solutions offered to solve this problem are digital literacy socialization, Merdeka Mengajar application training, and news writing workshops for website content. The aim is to increase teachers' knowledge and skills in using digital technology in learning and provide teachers with experience in managing digital content. The results of this service activity were an increase in the ICT infrastructure aspect by 100%, knowledge by 80% and digital skills by 80%.